Organisational behaviour, leadership and total quality management in private higher educational institutions (A Malaysian perspective) - Sukumaran, Sinnathamby (2011)
Organisational behaviour (OB) is the study and application of knowledge about how people, individuals, and groups act in organisations. A systematic approach is necessary to undertake the study of organisational behaviour in Private Higher Educational Institutions (PHEI) to achieve the status of Quality Higher Education Provider. That is it interprets people-organisation relationships in terms of whole person, whole group, whole organisation, and whole social system. Its purpose is to build better relationships by achieving human objectives, organisational objectives, and social objectives. Organisational behaviour encompasses a wide range of topics such as human behaviour, management style, leadership style, teamwork etc. This project paper focuses on attributes of Organisational Behaviour, Leadership and Total Quality Management for PHEls to achieve the status of ‘Quality Higher Education Provider’. The attributes are: 1. Elements of organisational behaviour 2. Models 3. Social systems 4. Organisational development 5. Work life ‘ 6. Action learning 7. Change 8- Quality Management System 9. Quality Management Tools Many Organisations not only in Malaysia but also in other parts of the world are currently great diﬁiculty in controlling and managing individuals, groups and whole of people behaviours. ln an organization, resources such as materials, machines, money, management styles, and market are controlled and